PRISCIANUS MINOR : GRAMMATICAL THEORY AND TECHNIQUE OF COMPOSITION (Argos, 2018)
In this article we give full details of the per figuram examples obtained through a novel method used in the elaboration of the DECOTGREL (Pmin) (2013). We have collected and systematize all ‘special uses’ documented in the so called Priscianus minor. With this method we have been able to find in these ancient treatises a lot of times suggestive remarks about facts which go further than a simple normative point of view and which have a great interest for a better knowledge of the language (Greek or Latin, for instance) as much as for a more detailed study of the evolution experienced by grammatical concepts and linguistic theories from the Antiquity to the Modernity
Keywords: Electronic Dictionary; DECOTGREL; Figure; Latin; Technical Lexicography